MAKNA LAGU YAA LAL WATHAN DALAM MENGKONSTRUKSI JIWA NASIONALISME SISWA MI NU HIDAYATUN NAJAH TUBAN - Fahrudi, Emi; Mundzir, Moh. (PREMIERE : Journal of Islamic Elementary Education, 2024)
Character Education for the next generation is a mandatory thing that must be considered seriously. It has become our responsibility to instilled nationalism character on young generation since elementary school age. The development of technology that influences lifestyle and family parenting models also contributes to the growth and development of nationalism construction in children which is increasingly eroded. Responding to this phenomenon, educational institutions become the second pillar after the family to design and construct children's nationalism. In this case, the Ma'arif NU educational institution designed a character education program to construct nationalism and a sense of love for the country through a mandatory program, namely singing the song “Yaa lal wathon” at every activity, both official and ceremonial, and making this song the second mandatory song after the song Indonesia Raya. In practice, this song has become a routine that makes students continue to sing the song. In this study, the researcher aims to reveal: (1) How is the interpretation of the meaning of the song "Yaa Lal Wathan" according to students of Madrasah Ibtidaiyyah NU Hidayatun Najah Tuban? (2) How is the impact of the song "Yaa Lal Wathan" in shaping the nationalism of students at Madrasah Ibtidaiyyah NU Hidayatun Najah Tuban Tuban? By using a phenomenological study approach, this study found that students interpreted the song as an inspiring song to protect the nation. This song is an indicator of the instillation of nationalism in students. The song "Yaa Lal Wathan" plays a role as an effective media in building students' nationalism, in accordance with Jean Piaget's cognitive development theory at the formal operational stage, where students begin to be able to think abstractly and hypothetically.